Productivity growth and sectoral interactions under Domar aggregation: A study for the Brazilian economy from 2000 to 2014 - Theo Santini; Ricardo Azevedo Araújo (Journal of Economic Structures, 2021)
In this paper, we use the Domar aggregation approach to study the evolution of Brazil's productivity growth from 2000 to 2014, thus allowing us a disaggregated assessment of the issue. We found that the Brazilian economy's overall performance is the outcome of a decrease in the economy's density, as defined by the existing backward and forward connections amongst industries in intermediate inputs chains. It also can be explained by the poor performance of its sectors. Despite the relatively high density of the manufacturing sector, it performed a negative role concerning aggregate productivity growth both directly and indirectly. Directly insofar as that sector had negatives productivity growths during the period under consideration, and indirectly due to its high interconnection, which spread negative rather than positive productivity gains across the economy. Therefore, to improve the Brazilian economy's poor performance, it is mandatory to restore the manufacturing sector's capability to yield and spread productivity gains.
Keywords: 330